Performance Analysis of Two Machine Transmission Network with PI Controller Based UPFC - Makkar, Deepak (My University, 2013)
With the rapid development of the power electronics industry, an increasing number of high power semiconductor devices are available for power system applications. These new devices have made it possible to consider new technologies such as Flexible Alternating Current Transmission Systems (FACTS). The Unified Power Flow Controller (UPFC) is versatile FACTS controller that can control three system parameters individually or simultaneously in appropriate combination. The work presented in this dissertation is concentrated on the two machine power system transmission model based on controlled voltage source. The model has been developed using MATLAB/SIMULINK. In this SIMULINK model consists of two parallel transmission lines, the one transmission line incorporating a UPFC and another is uncompensated. The overall aim is to control power flow by improving reactive power, voltage profile improvement and reduce the THD level in the transmission network. Simulation results of the model are analyzed.
ME, EIED
Keywords: UPFC; STATCOM; FACTS; SSSC